Valor prognóstico dos biomarcadores cardíacos e inflamatórios no câncer de cabeça e pescoço associados à terapêutica oncológica - Oliveira, Karine Gadioli de (2018)
Currently, cancer is the second largest cause of death in Brazil, surpassed only by cardiovascular diseases. Oncologic therapy has evolved and improved the prognosis in cancer patients. However, despite the unquestionable clinical benefit of this type of therapy, many of these drugs can cause undesirable side effects in the cardiovascular system. Head and neck cancer is the sixth most common cancer in the world and the prognosis for these types of patients is poor and has not improved in the last decades. Head and neck cancer patients have a high risk of non-cancer related mortality and one of the most frequent causes is cardiovascular disease. Therefore, the aim of this study was to evaluate the predictive value of C Reactive Protein (CRP), N-terminal pro–Btype natriuretic peptide (NT-proBNP), cardiac troponin T (cTnT), and cytokines (IL-17A, INF-γ, TNF-α, IL-10, IL-6, IL-4) in cardiovascular risk associated with oncologic therapy in head and neck squamous cell carcinoma. Thus, 118 patients with confirmed diagnosis of head and neck squamous cell carcinoma have been included in this study, and clinical-epidemiological data have been obtained with blood collection before and after cancer therapy.